GRATIFIKASI PELAYANAN SEKSUAL SEBAGAI TINDAK PIDANA KORUPSI - Mardiana Arsjad (JURNAL AKTA YUDISIA, 2021)
ABSTRACT           This thesis research aims to analyze one of the types of criminal acts of corruption contained in Law  Number  31  Year  1999  on  the  Eradication of Corruption which is amended by Law Number 20 Year  2001, which is about Gratification, in particular the provision of sexual service gifts in some  cases of corruption.The issues raised in this study are whether the provision of sexual services received by public servants or state officials can be categorized as gratification and become a criminal act  corruption. This study also aims to analyze the provision and regulation of legal sanctions for perpetrators of the gratificationof sexual services in Indonesia          This study uses the type of normative legal research (normative legal research) because it is still less clear about the regulation of gratification of sexual services as one of the criminal acts of corruption. The approach used in this study is the approach of legislation and conceptual aproach.                    Legal sanctions for Civil Servants and State Officials who commit corruption in accepting the gratification of sexual services may be charged under Article 5 paragraph (2), Article 12 letters a and b or Article 12B of Law Number 31 Year 1999 juncto Law Number 20 of 2001 when it meets its elemental elements. As for the gratification giver can be charged with Article 5 paragraph (1) of Law Number 31 Year 1999 juncto Law Number 20 Year 2001 and the sanction that can be applied to the object of sexual gratification law (women giving sex service) can be charged with article 15 Law Number 31 Year 1999 juncto Law Number 20 Year 2001. The recipients of gratification of sexual services and women who become the object of sexual services and the recipients of sexual services may also be charged under article 284 of the Criminal Code of moral decency if both fulfill the elements in the article. Keywords : Gratification of Sexual Services, Corruption, Proof, Legal sanctions